SEASONAL VARIATION OF GROUNDWATER LEVEL AND QUALITY IN XUAN MAI, HANOI, VIETNAM - Xuan Dung, Bui; Thi Kim Thanh, Do (Journal of Forestry Science and Technology, 2020)
Groundwater is the crucial source for domestic, agriculture, production in Xuan Mai town. To examine the seasonal variation of groundwater level and quality, four drill well was used to measure groundwater level in February and March 2017 (dry season) and from October 2018 to October 2019 (dry season 2018, dry season 2019 and wet season 2019). Otherwise, 12 drill well used to check groundwater quality from 2017 to April 2019. The groundwater quality was analyzed according to some indicators like pH, Fe, NO2-, NH4+, NO3-, CaCO3, TDS, Mn2+, Cl-, Asen. Groundwater quality index (GWQI) method also used to calculate pollution level. The quality results has compared with QCVN 09: 2015/BTNMT. The main results of this research include: (1) Groundwater depth experienced a fluctuation trend between two seasons which dry seasons was lower than wet ones by 10.67 %; (2) Pollution was detected in some parameters like NH4+ and Mn2+ of drill well 3 in both seasons in 2017 and 2019, which exceed 12 times and 1.3 times, respectively. In rainy season 2019, there was 2 more polluted indicators NO3- and Cl- in drill well 5, 6, 12; (3) According to groundwater quality index, the groundwater of drill well 3 was very poor in 2 seasons due to discharge from the factory in this area. The study provides specific information, a useful tool monitoring data of groundwater quality research to help authorities in planning appropriate strategies for sustainable management of groundwater resources.